First description and comparison of the morphological and ultramicro characteristics of the antennal sensilla of two fir longhorn beetles - Dong, Zishu (PLoS One, 2020)
Allotraeus asiaticus Schwarzer and Callidiellum villosulum Fairmaire are repeatedly intercepted in wood and wood products all over the world. As two common stem borers of Cunninghamia lanceolata (Lambert) Hooker, to further understanding of the differences in their living habits, behaviors and the mechanism of insect-host chemical communication, we observed the external morphology, number and distribution of antennal sensilla of A. asiaticus and C. villosulum with scanning electron microscopy (SEM), respectively. The results showed that 1st-5th subsegments of the flagellum are spined endoapically in A. asiaticus which is different from the previous report (1st-3rd of the flagellomere). Meanwhile, there were five subsegments on the flagellum of C. villosulum that were clearly specialized as serrated shapes on the 4th-8th flagellomeres. Four types (ten subtypes) of sensilla were both found on the antennae of these two fir longhorn beetles, named Böhm bristle (Bb), sensilla trichodea (ST I and II), sensilla basiconica (SB I, II and III), sensilla chaetica (SCh I, II, III and IV). There is one additional kind of morphological type of sensilla found on the antennae of C. villosulum compared to A. asiaticus which was related to their habit of laying eggs only on dry and injured fir branches, named sensilla campaniformia (SCa). These differences may vary according to their own biological habits. For research purposes, the observed difference in the sensillum distribution and function between the two fir longhorn beetles will greatly facilitate the design of better semiochemical control methods of these insect pests.